Thermal detection and robotic arm control - Mohamed Thalal Mohamed Thoufeek. (2010)
Rescue Robot has been built to enter the RoboCup 2010 competition. It involves detection of human based on several aspects like temperature, CO2 and etc. The detected humans are then localized for further rescue. The sensors are mounted on a swinging robotic arm mounted on the platform of the robot. My contribution for my final year project involves designing the dection based on thermal sensor and thr robotic arm.